Talent Migration Governance and the COVID-19 Pandemic: Comparing Germany and Singapore. Issue 1 (2nd January 2023) - Cerna, Lucie; Chou, Meng-Hsuan
ABSTRACT: We compare Germany and Singapore to see how their approaches toward talent migration governance have evolved in the last decade and whether and how the COVID-19 pandemic has affected these developments. Building on the Highly-Skilled Immigration Index (HSII), our discussions show Germany becoming very welcoming of high-skilled labor migrants, and Singapore becoming increasingly selective in which labor migrants it admits into the City State. Our findings reveal that the COVID-19 pandemic has not changed the direction of policies in Germany and Singapore, but it has affected talent migration rates.